International collaboration on forest genetic resources: the role of Europe: Second EUFORGEN Steering Committee meeting, 26-29 November 1998, Vienna, Austria - Turok, J.; Geburek, Th.; European Forest Genetic Resources Programme (2000)
The main objective of the Steering Committee meeting was to review the progress made since the establishment of the Programme in November 1994 and to outline future activities. EUFORGEN was developed as the implementation mechanism of Strasbourg Resolution S2 (Conservation of forest genetic resources) adopted at the first Ministerial Conference on the Protection of Forests in Europe. In his introductory remarks, Dr Geoffrey Hawtin, Director General of the International Plant Genetic Resources Institute (IPGRI) said that the conservation and sustainable use of forest genetic resources was a subject of global concern. The networking initiative of European countries gave substance to the implementation of Strasbourg Resolution S2, was essential for increasing the scientific knowledge in this area, and stimulated cooperation between national programmes in Europe and other regions. Ms Christel Palmberg-Lerche, Chief, Forest Resources Development Service, Forestry Department, United Nations Food and Agriculture Organization (FAO) also addressed the meeting. She underlined the importance of developing a coherent, country-driven global framework for the conservation, management, sustainable use and enhancement of forest genetic resources. The papers offered a broad overview of the current developments in the area of forest genetic resources and provided a basis for the further discussions specifically related to the role, orientation and management of the EUFORGEN Programme in the future. The workshop papers are published in this volume.